1999
DOI: 10.1074/jbc.274.10.6483
|View full text |Cite
|
Sign up to set email alerts
|

Early Phenotypic Changes in Transgenic Mice That Overexpress Different Mutants of Amyloid Precursor Protein in Brain

Abstract: (2) and London mutation(s) (3) alter APP processing, causing increased production of the A␤ peptide of 42 amino acids (4), hypothesized to be pivotal in AD pathology (1, 5). Early onset familial AD caused by mutations in the presenilin genes supports this hypothesis, because they increase production of A␤ (42) peptide (6, 7) due to the gain of an unknown function (8). The extensive cell biological definition of the metabolic effects of the different mutations in APP in vitro requires matching analysis of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
496
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 633 publications
(542 citation statements)
references
References 37 publications
(60 reference statements)
41
496
5
Order By: Relevance
“…Our results have shown that LTP was impaired in APPswe/PS1dE9 mice indeed, but it was normalized upon Hsp27 overexpression. There is substantial evidence from transgenic mouse models that intracellular Aβ initiates cellular dysfunction, synaptic, electrophysiological, and behavioral changes before it accumulates in extracellular plaques (Moechars et al 1999;Kumar-Singh et al 2000;Mucke et al 2000). The toxic Aβ molecules (either soluble oligomers or fibrillar forms) might initiate a cascade, which finally leads to neuronal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Our results have shown that LTP was impaired in APPswe/PS1dE9 mice indeed, but it was normalized upon Hsp27 overexpression. There is substantial evidence from transgenic mouse models that intracellular Aβ initiates cellular dysfunction, synaptic, electrophysiological, and behavioral changes before it accumulates in extracellular plaques (Moechars et al 1999;Kumar-Singh et al 2000;Mucke et al 2000). The toxic Aβ molecules (either soluble oligomers or fibrillar forms) might initiate a cascade, which finally leads to neuronal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological studies also indicate that Aβ oligomers can accumulate within neuronal processes (Takahashi et al, 2004;Kokubo et al, 2005). Several studies have demonstrated that soluble Aβ can disrupt synaptic function and impair LTP (Larson et al, 1999;Moechars et al, 1999;Chapman et al, 1999;Cleary et al, 2005). In support of the hypothesis that soluble Aβ can be neurotoxic, we also found decreases in synapse density in the outer molecular layer of the dentate gyrus in Tg2576 mice at an age when soluble Aβ is typically increased (i.e., 6-9 months of age), but when plaque deposition is minimal (Holcomb et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These animals exhibit significant levels of soluble A␤ in as few as 3 months of age, and extensive plaque deposition by 12 to 14 months. 45 Six- 44 ; open access article.) teen, 3-month-old, female mice were fed either a ketogenic chow or standard chow for 43 days.…”
Section: Ketogenic Dietsmentioning
confidence: 99%